The Internationalization Behavior of German High‐Tech Start‐ups: An Empirical Analysis of Key Resources. (January 2014) - Pinkwart, Andreas; Proksch, Dorian
Abstract Although there were a lot of new studies about the phenomenon of internationalization in the past several years, the field of newly founded technology‐based firms (NTBFs) internationalization was less considered in literature. We contributed in filling this research gap using a longitudinal study to discover the determinants of internationalization in Germany. Our sample was based on 116 venture capital–financed NTBFs; 44 of them went international. Given the high dependence on exports of the German economy, the internationalization behavior of its NTBFs is of great importance for the future macroeconomic development of the country. In comparison, there are still very few empirical studies on the key determinants and initial drivers for the rapid internationalization of German start‐ups. We showed that technological and financial factors are positively related to going global. The characteristics of the human capital, however, have no significance for going international in our sample. © 2013 Wiley Periodicals, Inc.